Host plants and antennal sensilla of Anomala testaceipennis Blanchard (Coleoptera: Scarabaeidae: Rutelinae) - Souza, Ana Caroline (2023)
This study was conducted at the Universidade Estadual de Mato Grosso do Sul, Cassilândia, Brazil from September 2017 to December 2021 in a Brazilian Cerrado. Adults of Anomala testaceipennis Blanchard were collected associated with host plants and taken to the laboratory for studies. Some phytophagous scarab beetles found host plants through detection of plant volatiles. The detection of those odorants is intermediated by antennal sensilla. The main goals of the present study are to describe the antennal sensilla of A. testaceipennis and check the host plants used as food resource. This specie was found feeding on flowers of: Anadenanthera colubrina var. cebil (Fabaceae), Azadirachta indica (Meliaceae), Buchenavia sp. (Combretaceae), Cordia glabrata (Boraginaceae), Inga edulis (Fabaceae), Moquilea tomentosa (Chrysobalanaceae), Paubrasilia echinata (Fabaceae), Tabernaemontana catharinensis (Apocynaceae), Tapirira guianensis (Anacardiaceae), Xylophragma pratense (Bignoniaceae). To the sensilla study, antennae were dissected and images of the sensilla were obtained using a scanning electron microscope. Antennae of A. testaceipennis have sensilla chaetica, trichodea, placodea (type I, II, and III), coeloconica (type I and II), basiconica (type I), and ampullacea (or pore). Males have a total of about 6,243 sensilla of which 5,868 (93.99%) are sensilla placodea, 370 (5.93%) are sensilla coeloconica, and 5 (0.08%) are sensilla basiconica. Females have a total of about 5,119 sensilla of which 4,820 (94.16%) are sensilla placodea, 270 (5.27%) are sensilla coeloconica, and 29 (0.57%) are sensilla basiconica.